THE ROLE AND IMPORTANCE OF VALUE ADDED TAX IN THE REVENUES OF THE STATE BUDGET OF UZBEKISTAN - Shirinov Sabir Erkinovich (Ecominds Press, 2025)
The article analyzes the current state of value-added taxation in Uzbekistan, including absolute values, growth rates, and the share of tax revenues, indirect taxes, and value-added tax in the state budget of Uzbekistan. The proportions of value-added tax and indirect taxes in the structure of tax revenues for the state budget of Uzbekistan were analyzed. It was determined that a significant portion of the state budget revenues of Uzbekistan is generated from value-added tax.
Keywords: Value added tax, tax base, tax object, absolute value, taxpayers, growth rate, share, indirect tax.